2021
DOI: 10.1055/s-0041-1740061
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Readmission after Early Postpartum Discharge during the COVID-19 Pandemic

Abstract: Objective To determine whether early postpartum discharge during the coronavirus disease 2019 (COVID-19) pandemic was associated with a change in the odds of maternal postpartum readmissions. Study Design This is a retrospective analysis of uncomplicated postpartum low-risk women in seven obstetrical units within a large New York health system. We compared the rate of postpartum readmissions within 6 weeks of delivery between two groups: low-risk women who had early postpartum discharge as part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This reduction may be the direct result of adaptations in discharge protocols to reduce the transmission of the virus and reduce the burden on hospital capacity and operations or may be the byproduct of inadvertent change to expedite the discharge process. This aligns with reports of decreased LOS specifically in low-risk and controlled delivery settings [34][35][36]. Few studies reported negative feelings and experiences of parents in the hospital setting during the pandemic, which could have affected LOS and expedited the discharge process, such as women not feeling safe giving birth, parents reporting themes of loneliness, emotional distress, adverse breastfeeding experiences, and unanticipated changes in hospital policies [37][38][39].…”
Section: Hospital Length Of Staysupporting
confidence: 75%
See 1 more Smart Citation
“…This reduction may be the direct result of adaptations in discharge protocols to reduce the transmission of the virus and reduce the burden on hospital capacity and operations or may be the byproduct of inadvertent change to expedite the discharge process. This aligns with reports of decreased LOS specifically in low-risk and controlled delivery settings [34][35][36]. Few studies reported negative feelings and experiences of parents in the hospital setting during the pandemic, which could have affected LOS and expedited the discharge process, such as women not feeling safe giving birth, parents reporting themes of loneliness, emotional distress, adverse breastfeeding experiences, and unanticipated changes in hospital policies [37][38][39].…”
Section: Hospital Length Of Staysupporting
confidence: 75%
“…Fourth, we did not have access to readmission data to assess downstream medical risks due to LOS reductions. Although data from one New York hospital system suggest that the LOS reduction was not offset by an increase in maternal readmissions in the 30 days after delivery, more research is needed to examine the longerterm consequences and safety of these pandemic-induced birth changes [35]. Fifth, we focused on the PTB type of indicated vs. spontaneous with the hypothesis that the pandemic affected many aspects of prenatal care delivery.…”
Section: Limitationsmentioning
confidence: 99%